Introductory Survey on Challenges Encountered by University Teachers in Online Teaching of STEM Subjects During COVID-19 Lockdown - Hadzieva, Elena; Guncaga, Jan; Bose, Subash Chandra; Ivanoska, Kalina Sotiroska (Central European Journal of Educational Research, 2021)
2020 will be remembered for COVID-19, a pandemic that forced the world to lock down and urged most educational providers to promptly implement e-learning solutions. In this paper, we point out some challenges faced by university teachers who had almost no earlier practice in online teaching. Nine lecturers working in different universities from Brazil, the Czech Republic, Estonia, Hungary, India, Macedonia, and Slovakia – all teaching science, technology, engineering, and mathematics (STEM) subjects – were interviewed to share their online teaching experiences during the COVID-19 lockdown. The aim of this introductory small-scale research paper is to provide a basis for future research regarding the influences that the COVID-19 situation has had on educational processes, as well as to assist educational providers in foreseeing and eliminating the possible problems of lecturers when establishing an online educational environment. Some conclusions are formulated from the interview survey, and possibilities for further research are described.